Disclosing quantitative RT-PCR raw data during manuscript submission: a call for action - Untergasser, Andreas; Hellemans, Jan; Pfaffl, Michael W; Ruijter, Jan M; van den Hoff, Maurice J B; Dragomir, Mihnea P; Adamoski, Douglas; Dias, Sandra Martha Gomes; Reis, Rui Manuel; Ferracin, Manuela; Dias-Neto, Emmanuel; Marsh, Ian; et al. (Molecular oncology, 2023)
Accuracy and transparency of scientific data are becoming more and more relevant with the increasing concern regarding the evaluation of data reproducibility in many research areas. This concern is also true for quantifying coding and noncoding RNAs, with the remarkable increase in publications reporting RNA profiling and sequencing studies. To address the problem, we propose the following recommendations: (a) accurate documentation of experimental procedures in Materials and methods (and not only in the supplementary information, as many journals have a strict mandate for making Materials and methods as visible as possible in the main text); (b) submission of RT-qPCR raw data for all experiments reported; and (c) adoption of a unified, simple format for submitted RT-qPCR raw data. The Real-time PCR Data Essential Spreadsheet Format (RDES) was created for this purpose.
Keywords: reprodukovatelnost výsledků; Real-Time Polymerase Chain Reaction; polymerázová řetězová reakce s reverzní transkripcí; Humans; lidé; RNA; Reverse Transcriptase Polymerase Chain Reaction; Reproducibility of Results; kvantitativní polymerázová řetězová reakce